IPTEKS PENGAWASAN TERHADAP REALISASI ANGGARAN DENGAN KONSEP GOOD GOVERNANCE DALAM MENCEGAH PRAKTEK KORUPSI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DAERAH PROVINSI SULAWESI UTARA - Tombokan, Andre Feral Adolf; Pangerapan, Sonny (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Indonesiaâs development depends on managing the budget state revenues and expenditures (APBN) therefore the government must be aware and change his character not to work alone without paying attention the interest or aspirations of the community. The purpose of this research is to know the flow or budget process at the public works agency and spatial planning in north Sulawesi province know the concept of good governance in carrying out supervision of realization budget, and to find out good governance in an effort to prevent corruption practices .this research is a qualitative research approach interpretive . the source of data from this study is primary data in the form of direct interviews, documentation and recording. Technique processing and analysis of data, namely the method of comparison by finding answers fundamental answers to cause and effect by analyzing factors the cause of the occurrence or emergence of a particular phenomenon. The result of this study indicate that the flow and budget process is on the PUPRD office in north Sulawesi, the budget planning process starts from conducting infestation field survey, after conducting surveys and data needed has been fulfilled, the budget calculation is carried out after it is entered planned DPA (budget implementation document) budget activities, after the DPA is published, we switch the process of physical implementation of work, including planning, design and so on,the concept of good governance in doing supervision of government budget realization is responsible for optimize the relationship between input and output. For example, for example public works agency, its input in the form of a budget can still be seen in its performance. Control,focused on how to utilize input minimum to produce the desired output that is in accordance with provisions and quality standards set at the time and quantity as which are desired. Keywords : supervision of budget realization